Pengaruh Pengaruh Store Atmosphere dan Accessibility Terhadap Revisit Intention Pada Coffee Shop Maru House Dengan Customer Experience Sebagai Variabel Mediasi Dalam Perspektif Bisnis Islam - Qoirullah, Aziz; Erike Anggraeni; Is Susanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of store atmosphere and accessibility on revisit intention with customer experience as a mediating variable at Maru House Coffee Shop in Bandar Lampung. Maru House is a unique coffee shop that combines a café environment with painting activities. However, in the midst of intense competition in the coffee shop industry, strategies are needed to maintain customer loyalty. This research adopts a quantitative approach using Structural Equation Modeling-Partial Least Square (SEM-PLS) and involves 91 respondents who have visited Maru House more than once. The analysis results indicate that both store atmosphere and accessibility have a positive and significant effect on customer experience. Furthermore, customer experience significantly influences revisit intention. It also partially mediates the relationship between store atmosphere and accessibility on revisit intention. In other words, while store atmosphere and accessibility have direct effects, customer experience strengthens the customers’ intention to return. From the perspective of Islamic business ethics, these findings are consistent with the principles of taysir (ease), ihsan (excellence in service), and maslahah (benefit), which emphasize the importance of comfort, ease of access, and quality service as forms of ethical behavior in business. By incorporating these values, Maru House Coffee Shop can enhance customer loyalty in an ethical and sustainable manner. This study contributes both theoretically and practically to the development of marketing strategies based on customer experience and Islamic business values in the café industry.